Neutrophilic inflammation in the respiratory mucosa predisposes to RSV infection - Habibi, Maximillian S. (2020)
The variable outcome of viral exposure is only partially explained by known factors. We administered respiratory syncytial virus (RSV) to 58 volunteers, of whom 57% became infected. Mucosal neutrophil activation before exposure was highly predictive of symptomatic RSV disease. This was associated with a rapid, presymptomatic decline in mucosal interleukin-17A (IL-17A) and other mediators. Conversely, those who resisted infection showed presymptomatic activation of IL-17– and tumor necrosis factor–related pathways. Vulnerability to infection was not associated with baseline microbiome but was reproduced in mice by preinfection chemokine-driven airway recruitment of neutrophils, which caused enhanced disease mediated by pulmonary CD8+ T cell infiltration. Thus, mucosal neutrophilic inflammation at the time of RSV exposure enhances susceptibility, revealing dynamic, time-dependent local immune responses before symptom onset and explaining the as-yet unpredictable outcomes of pathogen exposure.